THE LEGAL STATUS OF A PERSON AND HIS ROLE IN SOCIETY - Norqulov Muxtor Mavlonovich (Journal Park Publishing, 2024)
The concept of a "person" in society is a complex one, interwoven with legal frameworks, philosophical debates, and societal norms. This essay delves into the legal status of a person, exploring the intersection of individual rights, responsibilities, and the evolving nature of the social contract. We will examine how legal frameworks define personhood, the fundamental rights and obligations that accompany this status, and the ways in which societal shifts and technological advancements challenge our understanding of what it means to be a person within a community.
Keywords: legal status, laws, protection, individual, developing society, responsibilities